SOCIAL ECONOMIC LIFE “FAI WALU ANA HALO” IN THE COMMUNITY OF ENDE LIO FLORES - Dentis, Yosef (SEAN Institute, 2022)
Realizing the existence of the Fai Walu Ana Halo social classification, which literally means orphans and poor widows as a designation that has existed since the people of Lio Ende are familiar with local traditions and culture. This identity proves that the classification of social status is inherent in us since birth and is still valid today. Social identity can be related to the study of social stratification, namely the difference in population into social classes in stages, namely high class, middle class and low class. Fai Wal Ana Halo is a term for groups in the Lio Ende Ethnic community in cultured society, which means they are always cared for by Mosalaki Puu or the rulers of land and territories. They are cared for and get land for farming and plantations to support their economic life and land for housing.